DIALEKTOLOGI BAHASA MADURA DI DESA TAPAAN DAN DESA TLAGAH KECAMATAN BANYUATES KABUPATEN SAMPANG - Fatana Auliyah; Sri Utami; Nuril Huda (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2020)
Variations in languages found in Tapaan and Tlagah villages, both of theseareas are possible for data collection because these areas include coastal and mountainous areas which make a dialect factor. The formulation of the problem is how is the difference between Maduranese dialect in Tapaan village and Tlagah village in Banyuates subdistrict Sampang district? With the aim analyze the differences between Maduran dialect and Tapaan village, Tlagah village, Banyuates subdistrict, Sampang district. This research is a descriptive qualitative research with the power in the form of utterances or conversation which are then transcribed into written form in the form of words. The data is obtained from the original source of the study area in accordance with the data were researchers who were assisted by voice recording devices in the form of mobile phones. The data collection method in this research is the listening method and subsequent method uses a competent, free record, record method, record method, data transcription method, data transcription method, and translate data method. Next the researcher analyzes data that has been collected with the data element sorting technique, which is the matching method. Researchers also use data validity methods in the form of data validity methods, that is (a) prolong the participation of observations, (b) perseverance of observation, (c) tringualation. The results of this study obtained from research are the most common data in this study, namely the same word, but different in pronunciation, and there are also different words but the meaning is the same.